Ascertainment of uninterrupted CAG repeat length and disease-modifying variants in fragment-based genetic testing for Huntington Disease - Hailey Findlay Black; Chris Kay; Jessica Dawson; Stephanie Bortnick; Kyla Javier; Qingwen Xia; Cheuk Hin Chau; Tess Leavitt; Larissa Arning; Huu Phuc Nguyen; Michael R. Hayden (Genetics in Medicine Open, 2024)
ABSTRACT: Purpose: In Huntington disease (HD), synonymous variants causing loss or duplication of the interrupting CAA codon in the HTT CAG repeat modify disease onset. These variants are undetectable during HD genetic testing, resulting in inaccurate diagnostic reporting of uninterrupted CAG repeat length. Inaccurate reporting of CAG repeat length results in misdiagnosis of individuals with alleles near diagnostic cut-offs. We present a method to identify variant alleles during CAG repeat genotyping, allowing accurate diagnostic reporting of uninterrupted CAG repeat length. Methods: We used triplet-primed PCR (TP-PCR) to amplify HTT CAG repeat alleles with canonical or noncanonical repeat interruptions and leveraged differences in peak amplification patterns to develop a screening method based on peak height ratio (PHR). We used PHR to screen blood DNA from a cohort of symptomatic individuals with diagnostic CAG repeat lengths of 40 to 41. Results: TP-PCR enables accurate reporting of uninterrupted CAG repeat length in diagnostic testing by detecting HD alleles with loss or duplication of the CAG repeat interruption. Conclusion: PHR screening of TP-PCR traces is a cost-effective screening method for detection, ascertainment of uninterrupted HTT CAG repeat length, and accurate diagnostic reporting for individuals with disease-modifying noncanonical CAG repeat interruptions.